Hacking the Future of College Administration: Process Transformation through AR/VR Immersive Technology - Hastuty, Ade (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
The integration of immersive technologies such as augmented reality (AR) and virtual reality (VR) has changed the paradigm of administration in colleges. This technology has been proven to improve operational efficiency, reduce costs, and improve the stakeholder experience in various aspects, such as student enrollment, staff training, resource management, and virtual collaboration. This article evaluates the potential of AR and VR in simplifying administrative workflows, with a particular focus on Islamic colleges. Based on an analysis of 25 scientific sources, this article examines case studies, technological frameworks, and ethical considerations. The research highlights the importance of alignment with Islamic principles such as justice ('adl), benefits (maslahah), and morals. Challenges identified include implementation costs, limited access, technological literacy, and cultural resistance. In response, a number of recommendations were presented to support effective and sustainable adoption. The limitation of this research lies in the fact that no direct empirical tests have been conducted in Islamic higher education institutions, so the findings are still conceptual. This article offers a comprehensive starting framework for the use of immersive technology in creating an efficient, equitable, and contextual system of administration of cultural and religious values.